Vitality behind desolation: Characteristics and succession process of plant communities in the Chongqing special steel plant brownfield - Meng He; Bo Li; Xingyue Zeng; Chunlan Du; Jiajia Ding; Jie Lei; Wei Du; Chenglin Zhang (Ecological Indicators, 2024)
Phytoremediation is a sustainable way to clean contaminated urban soil, but selecting the right plants and designing communities is crucial. This study focuses on the vegetation in a disused steel plant in Chongqing, China, abandoned for nearly two decades. The goal is to reveal the plant community and succession patterns to inform the restoration of brownfield sites. This study combined the sample line and plot to investigate the vegetation and its growth environment in the Steel Plant. Information was recorded, including plant species, quantity, distribution, soil nutrients, humidity, and light. Cluster analysis categorized plant community types, and redundancy analysis examined the link between environmental conditions and plant types. The study found that: 1) There are 65 plant species (including 13 native trees) in the steel plant’s brownfield area, with Broussonetia papyrifera, Pteris vittata, and Debregeasia orientalis being the most abundant. The plants inside the plant were divided into seven groups based on species composition. 2) Soil moisture showed a significant positive correlation (Pearson index of 0.628) with plant survival, followed by a notable correlation with light intensity. 3) Environmental conditions partly influenced plant species composition and abundance variations. 4) 11 hyper-accumulating plant species were identified, focusing on three: the As hyper-accumulator Pteris vittata and the Cd hyper-accumulators Solanum nigrum and Debregeasia orientalis. The findings of this research will offer valuable insights for applying phytoremediation techniques in addressing contamination issues in brownfields within steel plants.